Determinants of Procurement Fraud (PBJ): Pentagon Approach and the Role of Anti-Fraud Awareness - Ratika Hanna Alfia; Sutrisno T; Lilik Purwanti (Eduvest - Journal of Universal Studies, 2025)
This study aims to understand the factors that encourage the occurrence of PBJ fraud in the public sector. The approach used refers to the Pentagon Fraud Theory, namely using financial pressure proxies, weak systems and procedures, moral justification, procurement committee capabilities, procurement committee egoism, and the role of anti-fraud awareness as a moderating variable. This study employs a quantitative approach with a survey method involving 143 respondents who are members of the Election Working Group (Pokja) at the Ministry of Public Works. Data analysis was carried out using the Partial Least Square–Structural Equation Modeling (PLS-SEM) approach with the SmartPLS 4.0 program. The results of the study show that financial pressure, weak systems and procedures, moral justification, procurement committee capabilities, and procurement committee egoism have a significant positive effect on PBJ fraud. The role of anti-fraud awareness has been proven to weaken the relationship between the Pentagon Fraud elements and PBJ fraud, except for the relationship between egoism and PBJ fraud, which was unproven. These findings affirm the importance of increasing anti-fraud awareness in preventing fraudulent acts and show that the Pentagon Fraud approach is relevant in analyzing the determinants of PBJ fraud. Overall, this research makes both empirical and practical contributions to efforts to strengthen the internal control system in the public sector.